THE EFFECT OF VACUUM PACKAGING ON CHANGES IN SENSORY, CHEMICAL AND MICROBIOLOGY QUALITY OF SMOKED CATFISH (Hemibagrus nemurus) STORED IN COLD TEMPERATURE (5±1°C) - Sri Aryati Rukmana Nasution; Bustari Hasan; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was aimed to determine the effect of vacuum packaging on sensory,chemical and microbiological quality of smoked catfish stored in cold temperatures (5±1°C). One hundrend fish which was taken from fish culture pond in Sungai Paku was hotsmokedat 60-100° C. The smoked fish was vacuum-packed in polypropilen bag and storedat 5±1° C for 49 days. Changes in quality were evaluated for sensoris, TBA, TVB-N, APC,ANPC, LAB and Staphylococcus aureus. The quality of vacuum-packed smoked fish duringstorage was compared to non-vacuum packed smoked fish. Sensory quality of vacuumpackedsmoked fish was not significantly different from non-vacuum packed smoked fish.TBA and TVB-N values were higher for non-vacuum packed smoked fish than for vacuumpacked smoked fish. APC value was also higher in non-vacuum packed smoked fish thanvacuum packed smoked fish, however ANPC and BAL were higher for vacuum packedsmoked fish than non-vacuum packed smoked fish; except Staphylococcus aureus countwhich were not different between the two smoked fish. Based on score 5 as a limit ofacceptibility, the vacuum packed smoked fish and non-vacuum packed smoked fish have ashelf life of 49 and 42 days respectively.Keywords: shelf life, smoked catfish, vacuum packaging,